2011
DOI: 10.3758/s13415-011-0041-2
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for unique threat-processing mechanisms in psychopathic and anxious individuals

Abstract: Behaviorally, psychopathy and anxiety display opposite patterns of threat sensitivity and response inhibition. However, it is unclear whether this is due to shared or to separate underlying processes. To address this question, we evaluated whether the threat sensitivity of psychopathic and anxious offenders relates to similar or different components of Gray and McNaughton’s (2000) Reinforcement Sensitivity Theory using a sample of 87 prisoners and a task that crossed threat onset with attentional focus. Psycho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 46 publications
0
10
0
Order By: Relevance
“…For example, people with clinical anxiety, such as specific phobia, exhibit extreme fear and hastened detection of relatively innocuous stimuli (for example, a photograph of a spider) 2 . On the other end of the spectrum, people with psychopathy have diminished threat detection and responsivity, which may contribute to antisocial behaviour 3 . This raises a question of how sensory information first reaches neural regions that elicit crucial, expedited responses to threats, and how might this be changed in people with symptomatically altered threat processing.…”
Section: Rapid Responses To Threatmentioning
confidence: 99%
“…For example, people with clinical anxiety, such as specific phobia, exhibit extreme fear and hastened detection of relatively innocuous stimuli (for example, a photograph of a spider) 2 . On the other end of the spectrum, people with psychopathy have diminished threat detection and responsivity, which may contribute to antisocial behaviour 3 . This raises a question of how sensory information first reaches neural regions that elicit crucial, expedited responses to threats, and how might this be changed in people with symptomatically altered threat processing.…”
Section: Rapid Responses To Threatmentioning
confidence: 99%
“…Newman and colleague have provided evidence that Factor 1 scores are associated with altered attention towards threat-related or peripheral stimuli during goal-directed behaviour (and altered early event-related scalp potentials) in samples of male prisoners (Baskin-Sommers, Curtin, Li, & Newman, 2012;Baskin-Sommers, Curtin, & Newman, 2011;Hamilton, Baskin-Sommers, & Newman, 2014). However, Lake et al (2011) reported that both Factor 1 and Factor 2 scores are associated with diminished fear-potentiated startle following the presentation of goaldirected cues (Lake, Baskin-Sommers, Li, Curtin, & Newman, 2011). In a smaller study of 43 adult male prisoners, Hansen et al found no association between any of the 4 PCL-R facets and recognition of facial expressions of fear (Hansen, Johnsen, Hart, Waage, & Thayer, 2008).…”
Section: Faces and Facets: Affective Deficits And Antisocial Behavioumentioning
confidence: 99%
“…The poor psychometric properties exhibited by FPS in this study indicate cause for concern in the previous literature (and a potential explanation for inconsistencies between studies), although it is possible that the application of stronger modulators or the restriction to clinical samples in some previous studies resulted in more reliable startle metrics. The numerous replicated direct links of FPS to clinical conditions and dispositional traits (Lake et al, 2011;Lang, 1995;Lissek, Powers et al, 2005;Vaidyanathan et al, 2009), its evolutionary conservation (Grillon & Bass, 2003), and its heritability in other species (McCaughran et al, 2000) suggest that some critical piece may yet be missing from the puzzle.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, SR is modulated in response to emotion‐ and fear‐relevant stimuli and is known to be augmented in threatening or negative affective states, with the higher SR during these states relative to neutral states being termed fear‐potentiated startle (FPS). FPS is a commonly used measure in psychophysiological research because it is thought to index subjective affective states and is linked to multiple domains of emotional functioning and psychopathology (Grillon & Bass, ; Lake, Baskin‐Sommers, Li, Curtin, & Newman, ; Lang, ), highlighting its relevance to the biological systems involved in fear and threat reactivity. Recently, researchers have begun to apply genetic approaches to investigate the etiology of FPS.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation